The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1074/jbc.272.18.12221
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Tyrosine Phosphorylation of c-Cbl and Associated Proteins in Phorbol Ester-resistant EL4 Mouse Thymoma Cells

Abstract: Two tyrosine phosphoproteins in phorbol ester-sensitive EL4 (S-EL4) mouse thymoma cells have been identified as the p120 c-Cbl protooncogene product and the p85 subunit of phosphatidylinositol 3-kinase. Tyrosine phosphorylation of p120 and p85 increased rapidly after phorbol ester stimulation. Phorbol ester-resistant EL4 (R-EL4) cells expressed comparable amounts of c-Cbl and phosphatidylinositol 3-kinase protein but greatly diminished tyrosine phosphorylation. Co-immunoprecipitation experiments revealed compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…These include adapter molecules such as Crk and Grb2 (10, 22, 25, 28 -30, 39, 40), PI 3-kinase (20,21,26,28,29,41,42), and the tyrosine kinases Fyn, Lyn, and Lck (26,27,29,31,36). Differences in proteins associated with Cbl may vary with the type of cell examined, or the receptor system examined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include adapter molecules such as Crk and Grb2 (10, 22, 25, 28 -30, 39, 40), PI 3-kinase (20,21,26,28,29,41,42), and the tyrosine kinases Fyn, Lyn, and Lck (26,27,29,31,36). Differences in proteins associated with Cbl may vary with the type of cell examined, or the receptor system examined.…”
Section: Resultsmentioning
confidence: 99%
“…Other investigators have demonstrated that Src-like kinases are able to bind to Cbl and that these interactions are mediated by the SH3 domain, the SH2 domain, or both (26,27,29,31,36). It is logical that the SH3 domain of Fyn could bind to Cbl in a phosphotyrosine-independent manner, since SH3 domains recognize proline-rich sequences, and there are several prolinerich regions in Cbl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses of “wild-type” (WT) PMA-sensitive EL4 cells to phorbol 12-myristate 13-acetate (PMA) include PKC activation [1–4], tyrosine phosphorylation [5,6], Erk activation [2,4,7,8], adhesion [9], IL-2 production [10–14], and growth arrest [4,11,13,15]. To study the mechanisms by which PMA elicits these responses, we and other groups have characterized PMA-resistant EL4 cells that proliferate in the presence of PMA [4,9,17].…”
Section: Introductionmentioning
confidence: 99%
“…Responses of sensitive "wild-type" (WT) EL4 cells to phorbol 12-myristate 13-acetate (PMA) include protein kinase C (PKC) activation (Kramer and Sando, 1986;Meier et al, 1991;Baier-Bitterlich et al, 1996;Sansbury et al, 1997), tyrosine phosphorylation (Richardson and Sando, 1995;Luo and Sando, 1997), Erk mitogen-activated protein kinase activation (Meier et al, 1991;Gause et al, 1993;Sansbury et al, 1997), adhesion (Resnick et al, 1997), IL-2 production (Farrar et al, 1980;Sando et al, 1982;Pearlstein et al, 1983;Harrison et al, 1987;Rayter et al, 1992), and growth arrest (Sando et al, 1982;Harrison et al, 1987;Desrivieres et al, 1997;Sansbury et al, 1997). To study the mechanisms by which PMA elicits these responses, we and other investigators have characterized PMA-resistant EL4 cells, which by definition proliferate in the presence of PMA (Resnick et al, 1997;Sansbury et al, 1997;Ku and Meier, 2000).…”
mentioning
confidence: 99%